Common Agricultural Policy Strategic Plans: Smokescreens or instruments for evidence-based policymaking? - Erjavec, Emil; Rac, Ilona; Bertolozzi-Caredio, Daniele (Italian Review of Agricultural Economics, 2025)
Alongside the devolution of decision-making powers to Member States, the latest reform of the Common Agricultural Policy (CAP) introduced CAP Strategic Plans to enhance the design and implementation of increasingly complex policy objectives and to reinforce the use of evidence-based policymaking (EBPM). This paper is based on desk research, combining a comparative review of European Union (EU) regulations and programming documents, and insights from the Tools4CAP project, which conducted interviews, surveys, and focus groups across Member States. The gaps in strategic planning are evident in the weak logical connection between individual phases of CSP preparation and the weak evidence-based justification of decisions regarding the selection and design of interventions. Quantitative tools and scientific evidence were underutilised, while political-economy constraints and path dependency dominated decision-making. As a result, CAP Strategic Plans were often developed through a series of disconnected tasks, producing documents with loosely linked sections lacking overall coherence. The upcoming integration of CAP planning into broader National and Regional Partnership Plans may simplify procedures but risks weakening EBPM principles. Systematic integration of science into planning, methodology development, interdisciplinarity, and better communication between researchers and decision-makers are needed to realise the ideal concept of EBPM. Institutional capacities for the use of evidence need to be strengthened, mandatory impact assessments and open data platforms introduced, and dialogue between science and policy enhanced. The limitations include reliance on secondary data and qualitative insights rather than detailed empirical evaluation across all Member States.